IMPLEMENTASI SISTEM BARCODE TERHADAP PELAKU UMKM DESA SUMBERBULU KECAMATAN MOJOGEDANG KABUPATEN KARANGANYAR - siswanta, Siswanta; Wangi, Maya Sekar (GANESHA: Jurnal Pengabdian Masyarakat, 2025)
Product marketing is one of the factors that concerns the existence of Micro, Small, and Medium Enterprises (MSMEs). Therefore, business actors, especially MSMEs, should be equipped with skills and knowledge regarding everything related to business communication, including how they understand marketing technology literacy. One form of implementing business communication tools that cannot be avoided is the utilization of barcode systems. The barcode system is not merely a binding between sellers and buyers. However, even broader than that, barcodes are used as a means of connecting business information based on communication technology. Related to the implementation of business communication technology, the common problem faced by MSME actors is the limited mastery of information technology and the limited understanding of business systems based on digital technology. To empower MSME actors, the service team offers a program to introduce barcode system implementation for MSME actors in Sumberbulu. Sumberbulu village in Mojogedang district. The target group aimed at consists of small and medium enterprises (SMEs), Sumberbulu village in Mojogedang district, Karanganyar regency. The execution technique begins with observations regarding the advantages and disadvantages inherent in the tourism SMEs of Sumberbulu village, which are then discussed through a brainstorming forum. The results of the discussion are used to formulate the needs and desires for strengthening SMEs. Data and information from the discussion are used as a basis for conducting short training on the implementation of Barcodes for micro, small, and medium enterprises (MSMEs). The importance of implementing the barcode system is not only related to the technical use of barcodes but also the critical attitude towards the system is very urgent so that MSME actors can avoid its negative impacts such as fraud, misuse of data, misleading information, and the like, which ultimately leads to potential financial and non-financial losses for MSME actors.